2020
DOI: 10.1017/fms.2020.40
|View full text |Cite
|
Sign up to set email alerts
|

Product formalisms for measures on spaces with binary tree structures: representation, visualization, and multiscale noise

Abstract: In this paper, we present a theoretical foundation for a representation of a data set as a measure in a very large hierarchically parametrized family of positive measures, whose parameters can be computed explicitly (rather than estimated by optimization), and illustrate its applicability to a wide range of data types. The preprocessing step then consists of representing data sets as simple measures. The theoretical foundation consists of a dyadic product formula representation lemma, and a visualization theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In [18] Kolaczyk and Nowak developed a systematic approach to multiscale probability models. They showed that multiscale factorizations, similar to Lemma 3.20 in [12] and the refomulation of it for dyadic measures on binary tree structured spaces, Lemma 2.1 in [2], arise when conditions for a "multiresolutionanalysis (MRA)" of likelihoods are satisfied and shown that these conditions characterize the Gaussian, Poisson and multinomial models. They also quantified the risk behavior of certain nonparametric, complexity penalized likelihood estimators based on their factorizations.…”
Section: Measures On Tree Structured Spacesmentioning
confidence: 97%
See 4 more Smart Citations
“…In [18] Kolaczyk and Nowak developed a systematic approach to multiscale probability models. They showed that multiscale factorizations, similar to Lemma 3.20 in [12] and the refomulation of it for dyadic measures on binary tree structured spaces, Lemma 2.1 in [2], arise when conditions for a "multiresolutionanalysis (MRA)" of likelihoods are satisfied and shown that these conditions characterize the Gaussian, Poisson and multinomial models. They also quantified the risk behavior of certain nonparametric, complexity penalized likelihood estimators based on their factorizations.…”
Section: Measures On Tree Structured Spacesmentioning
confidence: 97%
“…The product coefficient parameters uniquely determine the measure µ by the Dyadic Product Formula Representation ( Lemma 2.1) [2], even when the binary tree is infinite. The basic observation is that µ(S(n)) equals µ(D) multipled by the product of the factors from the root to a node n divided by 2 −scale(n) .…”
Section: Product Coefficients For Measures On Dyadic Setsmentioning
confidence: 99%
See 3 more Smart Citations